Diagnosis Penyakit Rubella Menggunakan Metode Fuzzy Tsukamoto - Widya Febriani; Gunadi Widi Nurcahyo; S Sumijan (Jurnal Sistim Informasi dan Teknologi, 2019)
Rubella or better known as German measles is a viral infection characterized by a red rash on the skin. Lack of general public understanding of this disease makes the number of patients with Rubella increasing. So Fuzzy Tsukamoto's method is used to detect Rubella disease. The purpose of this study is to facilitate the public in understanding about Rubella disease so as to reduce the number of sufferers of this disease. The first step to detecting Rubella disease is to determine the fuzzy set and the domain which includes 3 variables: red rash, swollen lymph nodes, and fever. The output of fuzzy calculations is someone experiencing Rubella or normal symptoms. The value obtained from the calculation process usig the Tsukamoto method is 6.00.